Violence against female health workers is tip of iceberg of gender power imbalances. (27th October 2020) - George, Asha S; McConville, Frances E; de Vries, Shaheem; Nigenda, Gustavo; Sarfraz, Shabnum; McIsaac, Michelle
Abstract : Tackling gender power relations is key to ensuring the safety and wellbeing of health workers and the ability to deliver quality care, say Asha George and colleagues